PERANCANGAN SISTEM INFORMASI MARKETPLACE USAHA MIKRO KECIL DAN MENENGAH DENGAN FOKUS PADA SISTEM KONSINYASI - Soegiarto, Richard; Meme Susilowati (Fakultas Sains dan Teknologi, 2024)
The digital market is increasingly becoming a foundation for Micro, Small and Medium Enterprises (MSMEs) in developing and marketing their products. This project report discusses the design and implementation of a marketplace information system specifically designed to support MSMEs. This system aims to increase visibility, accessibility and operational efficiency for MSME players, so that they can compete more effectively in the digital economy era. This project involves analyzing MSME needs, designing an intuitive user interface, integrating secure payment systems, and developing special features that support marketing and inventory management. In addition, this report discusses aspects of data security and customer privacy as an integral part of implementing a marketplace system. In the development process, thorough testing and evaluation was carried out to ensure system reliability and performance. The success of this project is measured through the parameters of user satisfaction, MSME sales growth and improved operational efficiency. The results of this project are expected to make a positive contribution to the growth of MSMEs, open up new opportunities for marketing local products, and increase their competitiveness in an increasingly connected global market. This project is a strategic step in supporting the digital transformation of MSMEs towards a more sustainable and inclusive future.